The Slow Industrial Take-Off of Bucaramanga, Colombia (1857-1929) - Acevedo Tarazona, Álvaro; Espinosa Suárez, Carlos Humberto (Universidad Pedagógica y Tecnológica de Colombia, 2020)
This article analyzes the conditions that made possible an incipient industrialization process in Bucaramanga, Colombia, for seven decades, five corresponding to the 19th century and two to the 20th century. The origin and amount of capital, the professions and occupations of economic actors, the level of risk used, the sense of association, business conduct, ownership and use of land and the various investment sectors are some of the factors  examined to understand why the Santander region failed to consolidate an industrial and commercial process similar to that experienced in the states of Antioquia and Valle del Cauca. Based on the concept of the merchant and its performance in economic sectors of production and marketing, its link in the cultural industry, banking, finance and construction, state policies and strategies to encourage industrialization at national level will be analyzed with the objective to show the progress made in Bucaramanga with reference to similar contexts. The analysis of notarial archives and of the local press as a primary source make possible to understand the economic process of Santander region between 1857 and 1929; for this, the consultation of notarial protocols, evidence of the constitution of companies and the transformation of capitals in Bucaramanga region was essential. This article opens a perspective for the realization of new studies that show the process of economic development in Santander and find out the reasons for its stagnation compared to other Colombian departments.